Factors of realization and differentiation scientific potencial of young scientists - SHELESTUN, KATYA (Journal of Education Culture and Society, 2020)
In domestic and foreign scientists’ research the scientific potential is investigated thro-ugh a series of economic indicators, but social and cultural aspects are not revealed. Scien-tists’ interest focuses primarily on the resource component of the scientific potential expres-sed through quantitative indexes (funding of science, number of academic staff involved in economics, the volume of scientific & technical work, etc.). The analyses of the current scientific literature have found that the concept of scientific potential with respect to young scientists has not been sufficiently studied.